2016
DOI: 10.1002/ijc.30220
|View full text |Cite
|
Sign up to set email alerts
|

PBX3 is a putative biomarker of aggressive prostate cancer

Abstract: There is a great need to identify new and better prognostic and predictive biomarkers to stratify prostate cancer patients for optimal treatment. The aims of this study were to characterize the expression profile of pre-B cell leukemia homeobox (PBX) transcription factors in prostate cancer with an emphasis on investigating whether PBX3 harbours any prognostic value. The expression profile of PBX3 and PBX1 in prostate tissue was determined by immunohistochemical and immunoblot analysis. Furthermore, the expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 31 publications
1
39
0
Order By: Relevance
“…22,23 TargetScan, miRDB, and TargetMiner revealed that genes other than LIN28B, such as CDC34, PBX3, and FZD3, were predicted as candidate miR-4500 targets. PBX3 is overexpressed in gastric cancer and prostate cancer 24,25 and promotes CRC migration by regulating the MAPK/ERK pathway. 26 CDC34 is highly expressed in multiple myeloma (MM) and associated with the growth and survival of MM cells.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 TargetScan, miRDB, and TargetMiner revealed that genes other than LIN28B, such as CDC34, PBX3, and FZD3, were predicted as candidate miR-4500 targets. PBX3 is overexpressed in gastric cancer and prostate cancer 24,25 and promotes CRC migration by regulating the MAPK/ERK pathway. 26 CDC34 is highly expressed in multiple myeloma (MM) and associated with the growth and survival of MM cells.…”
Section: Discussionmentioning
confidence: 99%
“…Because PBX1 was highly expressed in PCa tissues and cell lines, and its homolog PBX3 is a putative progressive biomarker in PCa (7), we wondered whether PBX1 was important for PCa cell proliferation and survival. To this end, we used DU145 that lacks PBX1 and PC3 that expresses PBX1 for next studies.…”
Section: Pbx1 Promotes Pca Cell Proliferationmentioning
confidence: 99%
“…In gastric carcinomas (5) and nonsmall cell lung cancers (6), PBX1 promotes epithelial to mesenchymal transition that is associated cro ARTICLE with chemoresistance. Although there are less studies on PBX1 in PCa, a recent study revealed that PBX3, a homolog of PBX1, is a putative biomarker of aggressive PCa (7). There are two PBX1 transcripts: PBX1a and PBX1b, between which the only difference is that PBX1b lacks the 7th exon (8), but their biological functions remain very similar as a transcription factor.…”
mentioning
confidence: 99%
“…It belongs to the TALE/PBXHOX family with a highly conserved homologous domain, which binds to the sequence 5′-ATCAATCAA-3′ by interacting with other homologous proteins (such asMEIS1 and HOXA9), resulting in transcription activation or target gene silencing [7,9,10]. Many reports demonstrated that aberrant expression of PBX3 was closely correlated with survival and tumor growth in patients with gastric and colorectal cancer [14][15][16]. Perturbing the PBX3 interaction with HOX or knockdown PBX3 induced apoptosis and inhibited epithelial-to-mesenchymal transition of tumor cells [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of PBX3 induces epithelial-mesenchymal transition and promotes invasion and metastasis of gastric, and colorectal cancer cells [13][14][15]. Moreover, elevated expression of PBX3 is associated with indolent progression to castration-resistant prostate cancer [16,17]. Targeting HOXA9/ PBX3 interaction has been suggested as a new therapeutic strategy to treat leukemia, gastrointestinal cancer, and nonsmall cell lung cancer [5,18,19].…”
Section: Introductionmentioning
confidence: 99%